2003
DOI: 10.1002/art.10848
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial peptidoglycans but not CpG oligodeoxynucleotides activate synovial fibroblasts by toll‐like receptor signaling

Abstract: Objective. To test the hypothesis that bacterial products acting as adjuvants, such as CpG oligodeoxynucleotides (ODNs) and peptidoglycans (PGs), are able to activate synoviocytes, and to determine the involvement of Toll-like receptors (TLRs) in this activation process.Methods Conclusion. We demonstrate that bacterial PGs activate synovial fibroblasts, at least partially via TLR-2, to express integrins, MMPs, and proinflammatory cytokines. Inhibition of TLR signaling pathways might therefore have a beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
149
4
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 40 publications
5
149
4
6
Order By: Relevance
“…Moreover, in our experiments, down-regulation of PBEF in RASFs by siRNA not only decreased basal IL-6, MMP-1, and MMP-3 levels but also significantly inhibited TLR ligand-induced production of cytokines and destructive enzymes. TLRs were shown to be key players in inflammatory and destructive processes in RA (3,4,20,25). TLR ligands of microbial origin as well as endogenous TLR ligands were demonstrated to be present in RA synovial fluid as possible drivers of inflammatory processes (1,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in our experiments, down-regulation of PBEF in RASFs by siRNA not only decreased basal IL-6, MMP-1, and MMP-3 levels but also significantly inhibited TLR ligand-induced production of cytokines and destructive enzymes. TLRs were shown to be key players in inflammatory and destructive processes in RA (3,4,20,25). TLR ligands of microbial origin as well as endogenous TLR ligands were demonstrated to be present in RA synovial fluid as possible drivers of inflammatory processes (1,26).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated that TLR-2, TLR-3, and TLR-4 ligands induce high amounts of cytokines and matrix-degrading enzymes in RASFs (3,5,20). In order to investigate whether PBEF is involved in the up-regulation of these effector molecules, we treated siPBEF-transfected RASFs with bLP, poly(I-C), and LPS, and analyzed the induction of IL-6, IL-8, MMP-1, and MMP-3, 24 hours after TLR ligand stimulation.…”
Section: Positive Correlation Of Pbef With the C-reactive Protein (Crmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study utilizing immunohistochemistry, both TLR-2 and TLR-4 were found to be expressed in the synovial tissue of patients with RA (16)(17)(18). Furthermore, in a study using reverse transcriptase-polymerase chain reaction (RT-PCR) and in situ hybridization, TLR-2 was found to be expressed in the rheumatoid joint and to be up-regulated in RA synovial fibroblasts by TNF␣ and IL-1␤ (8,19).…”
mentioning
confidence: 99%
“…Bacterial products known as pathogen-associated molecular patterns (PAMPs), such as lipopolysaccharide (LPS) or peptidoglycan, are known to activate FLS by interacting with cellular pattern-recognition receptors (PRRs) present on these cells (15,16). A large number of PRRs, such as Toll-like receptor 2 (TLR-2), TLR-4, and TLR-9, as well as numerous integrins are expressed by FLS, and their expression is increased in response to inflammatory stimuli (16,17). We previously showed that LPS, bacterial lipopeptide (BLP), and protein I/II, which are ligands of TLR-4, TLR-2, and ␣5␤1 integrin, respectively, can trigger the release of IL-6 and IL-8 from activated FLS (18,19).…”
mentioning
confidence: 99%